2022
DOI: 10.1093/nar/gkac360
|View full text |Cite
|
Sign up to set email alerts
|

Hexokinase 2 is a transcriptional target and a positive modulator of AHR signalling

Abstract: The aryl hydrocarbon receptor (AHR) regulates the expression of numerous genes in response to activation by agonists including xenobiotics. Although it is well appreciated that environmental signals and cell intrinsic features may modulate this transcriptional response, how it is mechanistically achieved remains poorly understood. We show that hexokinase 2 (HK2) a metabolic enzyme fuelling cancer cell growth, is a transcriptional target of AHR as well as a modulator of its activity. Expression of HK2 is positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 74 publications
0
6
0
Order By: Relevance
“…The relationships of estrogenic, antiestrogenic, and antiandrogenic activity of PAHs with endogenous AhR have been reported for several cells and reporter gene assays [6,15,22,23,25,27,33,43,53,54,56,67,68,70,71]. However, the effect of AhR on the AR inhibition and ER activation (the metabolites of compounds with CYPs and binding interaction between AhR and AR or ER) is predicted to be small in the present study with U2OS-luc cells [40,55,56].…”
Section: Endocrinological Risk Implications Of Oxy-pahs and Nitro-pahsmentioning
confidence: 61%
See 1 more Smart Citation
“…The relationships of estrogenic, antiestrogenic, and antiandrogenic activity of PAHs with endogenous AhR have been reported for several cells and reporter gene assays [6,15,22,23,25,27,33,43,53,54,56,67,68,70,71]. However, the effect of AhR on the AR inhibition and ER activation (the metabolites of compounds with CYPs and binding interaction between AhR and AR or ER) is predicted to be small in the present study with U2OS-luc cells [40,55,56].…”
Section: Endocrinological Risk Implications Of Oxy-pahs and Nitro-pahsmentioning
confidence: 61%
“…U2OS (osteoblast sarcoma) cells have low expression levels of AhR and CYPs. A small effect of AhR on AR inhibition activity (the metabolites of PAHs with CYPs and binding interaction between AhR and AR) is predicted [55]. For U2OS cells, the effect of AhR on ERα-activation has been reported: The change of expression amount in ERα-mediated activation was not caused by AhR ligand (i.e., dioxin) in CALUX assay with mammalian ERα-transfected U2OS-luc cells, if AhR was not transfected in these cells [56].…”
Section: Antiandrogenic Activity In the Calux Assaymentioning
confidence: 99%
“…Studies on the epigenetic regulation of the AhR pathway have shown that the AhR gene as well as the AhR-target genes are regulated by epigenetic modifications, including DNA methylation, histone modification and miRNA [ 18 ]. These regulations were shown to be relevant for cell-type specific expression and in different disease states such as cancer [ 61 , 62 ]. Concerning the AhR target gene CYP1A1, it was shown that dioxin leads to a decrease in the methylation of its promoter [ 63 ].…”
Section: Long-term Adaptation and Epigeneticsmentioning
confidence: 99%
“…The presence or absence of co-regulatory proteins and their activity levels influence both the basal transcription and ligand inducibility of AhR [ 55 , 56 ] ( Figure 1 ). Recently, hexokinase 2 was found to be a transcriptional target of AhR and a positive regulator of AhR-mediated transcription [ 57 ]. Important regulators of AhR signaling also include proteins such as AhRR [ 58 ], TiPARP [ 59 , 60 , 61 , 62 ], Gadd45b [ 63 ], p300, CREB binding protein (p300/CBP) [ 64 ], Smad3 [ 65 ], and SIN3A [ 66 , 67 ].…”
Section: Review Of Ahr Biology and Signalingmentioning
confidence: 99%